Boron Nitride Nanostructures: Fabrication, Functionalization and Applications - Yin, Jun; Li, Jidong; Hang, Yang; Yu, Jin; Tai, Guoan; Li, Xuemei; Zhang, Zhuhua; Guo, Wanlin (Small (Weinheim an der Bergstrasse, Germany), 2016)
Boron nitride (BN) structures are featured by their excellent thermal and chemical stability and unique electronic and optical properties. However, the lack of controlled synthesis of quality samples and the electrically insulating property largely prevent realizing the full potential of BN nanostructures. A comprehensive overview of the current status of the synthesis of two‐dimensional hexagonal BN sheets, three dimensional porous hexagonal BN materials and BN‐involved heterostructures is provided, highlighting the advantages of different synthetic methods. In addition, structural characterization, functionalizations and prospective applications of hexagonal BN sheets are intensively discussed. One‐dimensional BN nanoribbons and nanotubes are then discussed in terms of structure, fabrication and functionality. In particular, the existing routes in pursuit of tunable electronic and magnetic properties in various BN structures are surveyed, calling upon synergetic experimental and theoretical efforts to address the challenges for pioneering the applications of BN into functional devices. Finally, the progress in BN superstructures and novel B/N nanostructures is also briefly introduced. Boron nitride nanostructures have attracted intense attention for their excellent properties. Controlled synthesis of quality samples and the electrically insulating property largely prevents the realization of the full potential of BN nanostructures. The current status of the synthesis and applications of two dimensional h‐BN are reviewed, as well as versatile strategies in pursuit of tunable electronic and magnetic properties in BN nanostructures.